ผลของการปรับสภาพพื้นผิวต่อความแข็งแรงดึงระดับจุลภาคระหว่างเดือยฟันเสริมเส้นใยที่มีส่วนประกอบพื้นฐานเป็นไดเมทาคริเลตกับแกนฟันเรซินคอมโพสิต - ศริยา เศารยะ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
Objective: To evaluate microtensile bond strength between dimethacrylate-based fiber post and resin composite core after post surface treatment with chemical agents. Materials and methods: Ninety-six FRC Postec Plus were divided into 6 groups: group 1 no surface treatment; group 2 treatment with 37% phosphoric acid for 1 minute; group 3 treatment with 30% hydrogen peroxide for 10 minutes; group 4-6 treatment with 30%, 35%, 50% hydrogen peroxide for 1 minute, respectively. Surface morphology of one post in each group was examined by scanning electron microscope. The remaining fiber posts in each group were divided into 3 subgroups: subgroup 1 silanization; subgroup 2 application of bonding agent; subgroup 3 application of silane-bonding agent. The surface treated post was placed at the center of a cylindrical plastic tube. Multicore Flow was injected into the matrix band and light-activated. The post-core units were cut into twenty stick-shaped specimens per group for microtensile bond strength test. Modes of failure were classified by stereomicroscope. Data of microtensile bond strength were analyzed with two-way analysis of variances and Dunnett’s T3 at 95% confidence level. Results: Post surface treatment with chemical agents could significantly increase the microtensile bond strength (p<0.05). The application of silane-bonding agent resulted in higher microtensile bond strength than the application of bonding agent or silane only, respectively. Post surface treatment with 30% hydrogen peroxide for 1 minute followed by silane-bonding agent showed the highest microtensile bond strength. Conclusions: Surface treatment of dimethacrylate-based fiber post with chemical agents followed by silane and/or bonding agent can improve bond strength between fiber post and resin composite core.